2019
DOI: 10.1038/s41598-018-37480-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ultrastructural Properties of Human Carotid Atherosclerotic Plaques by Scanning Acoustic Microscopy, Micro-Computer Tomography, Scanning Electron Microscopy and Energy Dispersive X-Ray Spectroscopy

Abstract: Microcalcification is the precursor of vulnerability of plaques in humans. Visualization of such small structures in vivo with high spatial resolution is an unsolved issue. The goal of this study is to evaluate the potential of scanning acoustic microscopy (SAM) in the determination of atherosclerotic plaques with calcifications by validating this technique with micro-computer tomography (micro-CT), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). The fibrocalcific plaques wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…15 As we previously reported, scanning acoustic microscopy (SAM) may be considered as another optional imaging tool obtaining useful information about structural and mechanical information of atherosclerotic plaque. 8,16 SAM provides differentiation between collagen-rich areas and calcifi ed regions, so it may be benefi cial to determine high-risk lesions in clinics. In our study, we have enlarged the patient number and evaluated the plaque structure in the context of symptomatic or asymptomatic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 As we previously reported, scanning acoustic microscopy (SAM) may be considered as another optional imaging tool obtaining useful information about structural and mechanical information of atherosclerotic plaque. 8,16 SAM provides differentiation between collagen-rich areas and calcifi ed regions, so it may be benefi cial to determine high-risk lesions in clinics. In our study, we have enlarged the patient number and evaluated the plaque structure in the context of symptomatic or asymptomatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that scanning acoustic microscopy may be a useful clinical tool for the diagnosis of vulnerable plaques. 8 In this report, we have enlarged our patients number and we have evaluated the atherosclerotic plaque-calcifi cation volumes of the patients in the context of symptomatic or asymptomatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Hastaların nörolojik açıdan semptomatik olup olmadığı, internal karotis arter içerisindeki stenozun yüzdesi ve plağın radyolojik görüntüleme yöntemleri sonucunda ortaya çıkan morfolojik özellikleri gibi birçok faktör göz önünde bulundurularak hastalara açık cerrahi ya da girişimsel yöntemler ile tedavi seçenekleri sunulabilmektedir (2,3). Konu hakkında literatür her geçen gün gelişmekte, kılavuzlar güncellenmektedir.…”
Section: Introductionunclassified
“…Although this method offers high resolution, it is difficult to relate the observed region to traditional histology analysis. Recent advancements in Scanning Acoustic Microscopy (SAM) has induced considerable interest to this method for assessment of both histological and elastic properties using the same tissue section 13,14 . This technique demonstrates great concordance with histology analysis based on light microscopy 15,16 .…”
Section: Introductionmentioning
confidence: 99%